Forecasting Greenhouse Gas Emissions from Heavy Vehicles: A Case study of Semarang City - Mochamad Arief Budihardjo; Isaaf Fadhilah; Natasya Ghinna Humaira; Mochtar Hadiwidodo; Irawan Wisnu Wardhana; Bimastyaji Surya Ramadan (Universitas Diponegoro, 2021)
In Indonesia, transportation sector, specifically road transport consumed most energy compared to other sectors. Eventually, the energy consumption will increase due to the growth of vehicle number that also escalate emission. Vehicle emissions had been recognized as a significant contributor to atmospheric greenhouse gas (GHG) pollution. Heavy-duty vehicles are considered as main sources of vehicular emissions in most cities. Therefore, it is crucial to take into account heavy-duty vehicle emission projections in order to support policymakers to identify vehicle emissions and develop pollution control strategies. The aim of this study is to forecast heavy-duty vehicle population, vehicle kilometers travelled (VKT), fuel consumption, and heavy-duty vehicle emissions using data of Semarang City to illustrate greenhouse gas emission of big cities in Indonesia. Business as Usual (BAU) and The Intergovernmental Panel on Climate Change (IPCC) method were incorporated to determine vehicle emission projection. Heavy-duty vehicle emissions increase from 2021 to 2030 by 12.317 to 22.865 Gg CO2/year with amount trucks and buses emissions of 21.981,5 Gg CO2/year and 884,2 Gg CO2/year, respectively.